1975
DOI: 10.1111/1523-1747.ep12598119
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Amp And Psoriasis

Abstract: Evidence that an adenyl cyclase system is present in all mammalian epidermis is reviewed. This adenyl cyclase is stimulated by at least two separate types of chemicals: catecholamines, which act at a beta-adrenergic receptor site, and prostaglandins of the E series, which act at a separate site. In the psoriatic lesion, the response to these stimulators, especially to the catecholamines, is reduced. Despite this lack of response to external agents which elevate cyclic AMP, the concentration of cyclic AMP withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

1976
1976
1986
1986

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…We also agree with the recent conclusion of Marcelo et al (1979) and with the previous reports of Yoshikawa et al (1975b) and Halprin et al (1975) that cAMP levels in lesional skin do not differ significantly from those in non-involved skin. We could not, however, confirm the finding of the Michigan group that the cAMP content of all psoriatic epidermis is decreased compared to the normal epidermis.…”
supporting
confidence: 94%
“…We also agree with the recent conclusion of Marcelo et al (1979) and with the previous reports of Yoshikawa et al (1975b) and Halprin et al (1975) that cAMP levels in lesional skin do not differ significantly from those in non-involved skin. We could not, however, confirm the finding of the Michigan group that the cAMP content of all psoriatic epidermis is decreased compared to the normal epidermis.…”
supporting
confidence: 94%
“…Other works have exclusively dealt with cAMP [Harkônen et al, 1974;Halprin et al, 1975], However, considering the utilization of different methods for tissue preparation and cAMP assay, the results and their interpretation are inconsistent. In a more recent work, where the epidermal area is frozen in vivo by application of liquid nitrogen and the biopsies taken without anesthesia, Adachi et al [1980] found no difference in basal cAMP level between normal and uninvolved psoriatic tissue, and a mild increase of this compound in involved psoriatic epidermis.…”
Section: Discussionmentioning
confidence: 99%
“…There are four stimulators linked to adenylatecyclase receptors in the plasma membrane of human (1)(2)(3)(4) and pig (5)(6)(7)(8) There are four stimulators linked to adenylatecyclase receptors in the plasma membrane of human (1)(2)(3)(4) and pig (5)(6)(7)(8) …”
Section: Introductionmentioning
confidence: 99%